KEBIJAKAN FISKAL ABU BAKAR DAN UMAR BIN KHATTAB - Okta Pendra; Aprinaldi, Pepi Yanti, Fuja Pelawati (CV. Adiba Aisha Amira, 2024)
Fiscal policy is the most important instrument in eflorts to realize the welfare of society and the people as a whole. In setting sharia standards, Umar Bin Khattab and Abu Bakar have made important commitments through their monetary arrangements. The financial approach directs the inflow and outflow of state funds. Abu Bakar provides social assistance to Muslims, especially the elderly, making the transition to Islam and the poor through the continuous use of zakat and zakat. Muslims are not required to pay these fees, while non-Muslims are required to pay these fees. In addition, Umar Bin Khattab recorded progress by establishing a money- related institution, Baitul Mal, which plays a role in maintaining financial health and emphasizing the government's obligations towards its citizens. This research aims to analyze fiscal policy during the time of Abu Bakar and Umar Bin Khattab for the welfare of the people and society from an Islamic perspective. The research method used is a qualitative library research approach, using relevant books and literature. The results of this research can increase understanding of the impact of money- related approaches on community welfare, the adequacy of social assistance, and the versatility of budgets obtained through education such as baitul mal.